Penerapan Metode SQ3R Dalam Pembelajaran Menulis Kembali Teks Biografi (Penelitian Kualitatif di PPS Ulya Imam Syafi'i Batam) - Ady Triyanto (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
Writing skills are one of four language skills that cannot be excluded from a student and the world of education. These skills are obtained from a learning process. This process can be done alone or in groups. However, in reality, students' mastery of this skill is very low. This is because this skill requires creativity to express ideas into writing. Writing skills cannot be acquired instantly, but require continuous training and practice. This writing skill must also be supported by reading comprehension skills to increase insight, intelligence and knowledge. The aim of this research is to improve the ability to rewrite biographical texts using the SQ3R reading comprehension method. This research activity was carried out by researchers who acted as human instruments for class X students at the Ulya Imam Syafi'i Islamic Boarding School, Batam. This research was conducted using a qualitative descriptive method. This activity is carried out by delivering material regarding the SQ3R method and practicing it directly by rewriting the biographical text using your own ideas and language style. The results of research regarding the application of the SQ3R method to students have had an impact on increasing their ability to re-write biographical texts. This improvement causes them to be able to understand the biographical text they read using the SQ3R method.